Effect of Fluorine Doping on the Electrochemistry and Structural Stability of Single‐Particle LiNiO2 - ELmaataouy, Elhoucine; EL Kassaoui, Majid; ELmouhinni, Mohamed; Kubota, Kei; Chari, Abdlewahed; Aqil, Mohamed; Sghiouri, Adil; Alami, Jones; Mounkachi, Omar; Dahbi, Mouad (ChemSusChem, 2025)
It is widely acknowledged that single‐particle LiNiO2 represents an attractive option as a cobalt‐free cathode material, given its high capacity and average working voltage. However, prolonged cell cycling has been observed to result in a decline in performance and structural deterioration in LiNiO2 cathodes. Anion doping has recently been the subject of considerable interest due to the numerous benefits it offers, including the elimination of the need for active element replacement and increased structural stability. In this study, a fluorine‐doped single‐particle LiNiO2 is prepared via a hydrothermal synthesis assisted by ball milling, resulting in a stable charge/discharge process at a current density of 0.2C, with a capacity retention of 90% after 60 cycles and first discharge capacity of 220 mAh g−1. The incorporation of fluorine is confirmed through cross‐sectional scanning electron microscopy and X‐ray photoelectron spectroscopy, which reveal a correlation between fluorine doping and the partial reduction of Ni3+ to Ni2+. The impact of fluorine doping on the structural stability of LiNiO2 is investigated using in‐situ X‐ray diffraction XRD and density functional theory calculations. Consequently, the F doping strategy demonstrates the dual benefit of high capacity and cycle retention in single‐particle LiNiO2 cathodes. The application of LiNiO2 as a cobalt‐free cathode for lithium‐ion batteries is a promising direction for sustainable energy. However, its electrochemical performance and structural stability during cycling remain limited. F doping can significantly improve the charge‐discharge cycling performance of LiNiO2 cathodes while also preventing irreversible phase transitions, enhancing both stability and efficiency.